2002
DOI: 10.1681/asn.v132453
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of End-Stage Renal Disease in Familial IgA Nephropathy

Abstract: ABSTRACT. Primary IgA nephropathy (IgAN) is characterized by recurrent episodes of macroscopic hematuria accompanied by upper respiratory tract infections or persistent asymptomatic microscopic hematuria with or without proteinuria. IgAN may involve one or more members of a family. Three generations of a cohort of 110 patients with biopsy-proven IgAN, living in Southern Italy, were checked for urinalysis, and the relative risk (RR) of developing the disease was evaluated. A total of 19 unrelated familial, 37 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our observation indicates that the prevalence of positive-FH was 11.6% among histologically proven, primary IgAN cases. The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our observation indicates that the prevalence of positive-FH was 11.6% among histologically proven, primary IgAN cases. The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ].…”
Section: Discussionsupporting
confidence: 81%
“…Of note, we could not find any difference in the age of onset and MEST-C score at initial biopsy. However, familial cases were diagnosed younger and showed histologically milder disease at an earlier stage, pointing to the importance of earlier diagnosis [ 5 , 8 , 15 ]. More attention for familial clustering and active screening of family members for eGFR and urinalysis are recommended in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IgAN mainly manifests as the deposition of IgA in the glomeruli, a disease that is mediated by immune complexes ( Rodrigues, Haas & Reich, 2017 ). IgA deposition in the mesangial region of the glomerulus causes inflammation that promotes mesangial proliferation and interstitial damage, which progresses to end-stage renal disease (ESRD) in nearly 40% of patients, although some patients maintain stable renal function for many years ( Schena et al, 2002 ). Patients with IgAN have many different clinical manifestations, ranging from asymptomatic hematuria and proteinuria to massive proteinuria to acute renal failure ( D’Amico, 2004 ).…”
Section: Introductionmentioning
confidence: 99%